Distinguishing chronic inflammatory demyelinating polyneuropathy from diabetic neuropathy: A case series from Northeast India (Indian Journal of Case Reports, 2025)
Chronic inflammatory demyelinating polyneuropathy (CIDP) is an immune-mediated neuropathy that may mimic diabetic sensorimotor polyneuropathy. Timely identification of CIDP in diabetics is critical, as it is potentially reversible with immunotherapy. We report a case series of three diabetic patients presenting with subacute progressive lower limb weakness. All three showed demyelinating features on nerve conduction studies and elevated cerebrospinal fluid (CSF) protein, consistent with albuminocytologic dissociation. Two cases showed classical electrophysiological features of CIDP, whereas one case had bilateral sural nerve involvement, conventionally suggestive of diabetic neuropathy, but responded dramatically to intravenous immunoglobulin. All three patients had functional recovery and improved nerve conduction post-treatment. Differentiating CIDP from diabetic neuropathy is essential, especially in the presence of atypical features or progression. Elevated CSF protein and treatment response remain key diagnostic clues, even in patients with features typically attributed to diabetes.